Requirement Engineering Challenges in Agile Software Development - Rasheed, Aqsa; Zafar, Bushra; Shehryar, Tehmina; Aslam, Naila Aiman; Sajid, Muhammad; Ali, Nouman; Dar, Saadat Hanif; Khalid, Samina (Mathematical problems in engineering, 2021)
Agile software development has large success rate due to its benefits and promising nature but natively where the size of the project is small. Requirement engineering (RE) is crucial as in each software development life cycle, “Requirements” play a vital role. Though agile provides values to customer’s business needs, changing requirement, and interaction, we also have to face impediments in agile, many of which are related to requirement challenges. This article aims to find out the challenges being faced during requirement engineering of agile projects. Many research studies have been conducted on requirement challenges which are somehow biased, no suggestions are given to improve the agile development process, and the research does not highlight large-scale agile development challenges. Hence, this article covers all the challenges discussed above and presents a comprehensive overview of agile models from requirement engineering perspective. The findings and results can be very helpful for software industry to improve development process as well as for researchers who want to work further in this direction.